2013
DOI: 10.1038/gene.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Differential CTLA-4 expression in human CD4+ versus CD8+ T cells is associated with increased NFAT1 and inhibition of CD4+ proliferation

Abstract: CTLA-4 is a costimulatory molecule that negatively regulates T cell activation. Originally identified in murine CD8+ T cells, it has been found to be rapidly induced on human T cells. Furthermore, CTLA-4 is expressed on regulatory T cells (Tregs). Clinically, targeting CTLA-4 has clinical utility in the treatment of melanoma. Whether the expression of CTLA-4 is differentially regulated in CD8+ vs. CD4+ human T cells is unclear. Here we analyzed CTLA-4 in normal human CD4+ and CD8+ T cell subsets and show for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 58 publications
9
75
0
1
Order By: Relevance
“…The lack of changes in the overall CD8 subpopulations had been previously observed in frozen samples at later time points [30]. Our data confirms that ipilimumab may be acting preferentially on CD4 T cells, which are known to express higher levels of CTLA-4 [32]. …”
Section: Discussionsupporting
confidence: 89%
“…The lack of changes in the overall CD8 subpopulations had been previously observed in frozen samples at later time points [30]. Our data confirms that ipilimumab may be acting preferentially on CD4 T cells, which are known to express higher levels of CTLA-4 [32]. …”
Section: Discussionsupporting
confidence: 89%
“…Data from a recent publication demonstrated that NFAT1 increased CTLA-4 promoter activity in CD4 + T cells compared with CD8 + T cells. The expression of CTLA-4 mediated by NFAT1 in CD4 + can potentially be important for anti–CTLA-4 therapy (29). Our laboratory has previously demonstrated that Gal-3 regulates autotaxin through NFAT1 and that high levels of Gal-3 support melanoma growth and metastasis (9).…”
Section: Discussionmentioning
confidence: 99%
“…The ergotope peptide-induced Treg cells secreted high levels of IL-10, but not TGF-β, and they were very strong suppressors of CD4 + CD25-effector T cell proliferation. Ergotope peptide treatment increased the surface and intracellular expression of CTLA-4, a costimulatory molecule that negatively regulates T cell activation, in CD4 + CD25 + Treg rather than in CD4 + CD25-T cells (46). CTLA-4 is constitutively expressed by CD4 + CD25 + FOXP3 + Treg and blockade of CTLA-4 interferes with Treg function (47).…”
Section: Resultsmentioning
confidence: 99%